Rewrite Equations to Solve for Y
Rewrite Equations to Solve for Y - How it Works - Video
Rewrite Equations to Solve for Y - How it Works - Video
Example 1
Example 1
Example 1:
We need to solve for y. Right now we have a coefficient of 3 and we need a coefficient of 1. So our first step is to divide both sides by 3.
3y = 2x + 6
y = (2x + 6)/3
y = 2/3 * x + 6/3
y = 2/3 *x + 2
Given
Divided both sides by 3
Separated into two fractions
Simplified
Example 2
Example 2
Example 2:
We need to solve for y. Right now we have a coefficient of 3 and we need a coefficient of 1. So our first step is to divide both sides by 3.
6x - 2y = 7
-2y = -6x + 7
y = -3x - 7/2
Given
Subtracted both sides by 6x
Divided each term by -2
Live Worksheet
Live Worksheet